Enteral nutritional support combined with fine-tuned nursing care improves nutritional status and postoperative complications in NICU patients with dysphagia - Dai, Tingting; Shi, Liangyu; Wang, Dongmei; Wang, Yan (Frontiers in Surgery, 2025)
This study focused on the effect of enteral nutrition support combined with fine-tuned nursing care on nutritional status and postoperative complications of patients with dysphagia in the Neurosurgical Intensive Care Unit (NICU). Ninety-eight patients who developed dysphagia from May 2021 to May 2023 in the NICU of our hospital were included in this study. They were randomly divided into a control group and a study group; the control group was given conventional care and the experimental group was given enteral nutrition combined with fine-tuned care. The hospitalization time, nutritional status, complications, Acute Physiology and Chronic Health Evaluation (APACHE) II score, Self-rating Anxiety Scale (SAS) score and nursing satisfaction were compared between the two groups. The findings indicated that enteral nutrition combined with fine-tuned care could effectively reduce the hospitalization time and complications, improve the nutritional supply and patient satisfaction, and reduce the APACHE II score and SAS score. In conclusion, enteral nutrition combined with fine-tuned care can effectively improve the nutritional status and postoperative complications of NICU dysphagia patients.